2017
DOI: 10.1371/journal.pone.0183390
|View full text |Cite
|
Sign up to set email alerts
|

Bispecific T cell engager (BiTE®) antibody constructs can mediate bystander tumor cell killing

Abstract: For targets that are homogenously expressed, such as CD19 on cells of the B lymphocyte lineage, immunotherapies can be highly effective. Targeting CD19 with blinatumomab, a CD19/CD3 bispecific antibody construct (BiTE®), or with chimeric antigen receptor T cells (CAR-T) has shown great promise for treating certain CD19-positive hematological malignancies. In contrast, solid tumors with heterogeneous expression of the tumor-associated antigen (TAA) may present a challenge for targeted therapies. To prevent esca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(63 citation statements)
references
References 49 publications
2
60
1
Order By: Relevance
“…In addition, the potency of either bispecific T-cell engager (BiTE) constructs or CAR-T cells depends on guiding the T cell to antigenpositive tumor cells. Bystander effects for BiTEs have therefore been reported to be dependent on proximity of the cytotoxic T cell to the target-negative tumor cell (37). Indeed, when in vivo activity of BAY 2287411 was tested in tumor models with varying target heterogeneity, in vivo activity was observed at H-scores as low as 25 and 80.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the potency of either bispecific T-cell engager (BiTE) constructs or CAR-T cells depends on guiding the T cell to antigenpositive tumor cells. Bystander effects for BiTEs have therefore been reported to be dependent on proximity of the cytotoxic T cell to the target-negative tumor cell (37). Indeed, when in vivo activity of BAY 2287411 was tested in tumor models with varying target heterogeneity, in vivo activity was observed at H-scores as low as 25 and 80.…”
Section: Discussionmentioning
confidence: 99%
“…Because formation of the cytolytic synapse is independent of standard antigen recognition and costimulation mediated by major histocompatibility complex class I, lysis of the target tumor cell occurs in a manner that is independent of immune escape mechanisms that tumor cells may develop to evade detection. CD3ε is expressed by all CD8 + and CD4 + T cells, which enables polyclonal T-cell activation, expansion, cytokine production, and tumor cell lysis [51].…”
Section: Bispecific Antibody Constructsmentioning
confidence: 99%
“…Another positive effect of arming OVs with T-cell engagers is the bystander effect demonstrated in specific cases. It has been shown that tumor cells negative for the target molecule of the engager (in this case EGFR) were lysed when in proximity to tumor cells that display the target antigen through T-cell induced bystander cell lysis ( 40 ). A phase II clinical trial has been reported for T-cell engager molecules which showed promising initial results but leaves room for improvement in terms of delivery regime in order to reduce the number of patients who need to drop out of the treatment early due to side effects.…”
Section: Strategies To Improve the Induction Of Tumor-specific Immunimentioning
confidence: 99%